Genetic Diversity and Population Size Change of Balanites aegyptiaca (L.) Delile Natural Populations - Lucky Dartsa Wakawa; Adejoke Olukemi Akinyele (South-East European Forestry, 2025)
Balanites aegyptiaca is an underutilized wild fruit tree with significant ethnomedicinal value. However, the species' population is under threat from overexploitation, and if action is not taken, the species could become extinct in the near future. Understanding the molecular properties and population dynamics of the species is crucial for devising effective plans for its domestication and conservation. This study aimed to evaluate the diversity of Balanites aegyptiaca within its native Nigerian populations to identify suitable sources for its domestication and conservation. Leaf samples had their DNA extracted using a standard method. Molecular analysis was conducted utilizing chloroplast DNA sequences from the matK gene area. Software programs MEGA and DnaSP were employed to construct a phylogenetic tree as well as calculate pairwise genetic distance, nucleotide diversity (Pi), haplotype diversity (Hd), the number of variable sites (S), parsimony-informative sites (Ps), average nucleotide differences and changes in population size. The genetic diversity was found to vary among the population based on the nucleotide diversity (Pi) index measured. The highest Pi value was 0.264 in the Mashi population. Parsimony-informative sites ranged from 0.0 at Dumsai to 2.0 at Mashi. Variable site number ranged from 3.0 at Dumsai to 302.0 at Mashi, while the average number of nucleotide differences ranged from 2.0 at Dumsai to 151.7 at Mashi. In Buratai, a unimodal distribution curve was found, suggesting population expansion, whereas the other sources displayed bimodal and multimodal distribution curves, indicating minimal population changes. The high genetic trait recorded by the Mashi population is indicative of high genetic diversity within the population, and it could serve as a potential source of superior genetic material required for the conservation of Balanites aegyptiaca.